Penguatan Generasi Berencana (GenRe) pada Mahasiswa Program Studi Ilmu Kesehatan Masyarakat Universitas JambiSchool is a means of learning for every student including adolescents, including universities. Teenagers who are studying in college are in a tran - Fitri, Adelina; Wulansari, Arnati; Rahmat, Andree Aulia; Rahim, Beny; Mekeama, Luri; Putra, Ashar Nuzulul (Poltekkes Kemenkes Jambi, 2025)
School is a means of learning for every student including adolescents, including universities. Teenagers who are studying in college are in a transition period towards the adult phase. In this phase adolescents often try new things that are quite different and challenging. It is not uncommon to find teenagers disappearing from lecture activities due to pregnancy outside of marriage, starting to try smoking, stumbling over drugs, and undeniably getting into motorcycle gangs. Thus, this community service program will provide Strengthening Generation Planning (GenRe) to Jambi University Public Health Science Study Program Students. It is hoped that with this activity adolescents will have good knowledge and have more directed life goals in the future. After the education, students' knowledge increased, which can be seen from the average increase from 98.44 to 100. The smallest score was also seen to have increased before the psychoeducation on family readiness, namely 90 to 100. From the results of the Wilcoxon test, sig (2-tailed) 0.025 <0.05 was obtained, which means that there is an effect of providing education on student knowledge of Strengthening Generation Planning (GenRe) in Jambi University Public Health Science Study.